Characterising Deadlines in Temporal Modal Defeasible Logic - Governatori, Guido; Hulstijn, Joris; Riveret, Régis; Rotolo, Antonino (AI 2007: Advances in Artificial Intelligence, 2007)
We provide a conceptual analysis of several kinds of deadlines, represented in Temporal Modal Defeasible Logic. The paper presents a typology of deadlines, based on the following parameters: deontic operator, maintenance or achievement, presence or absence of sanctions, and persistence after the deadline. The deadline types are illustrated by a set of examples.